Contemporary evolution of an invasive plant is associated with climate but not with herbivory. (6th June 2015) - Colomer‐Ventura, Ferran; Martínez‐Vilalta, Jordi; Zuccarini, Paolo; Escolà, Anna; Armengot, Laura; Castells, Eva
Summary: Divergence in plant traits and trait plasticity after invasion has been proposed as mechanisms favouring invasion success. Current hypotheses predict a rapid evolution in response to changes in the abiotic conditions in the area of introduction or to differences in the herbivore consumption pressure caused by a decrease in the enemies associated with the area of origin [e.g. evolution of increased competitive ability (EICA) hypothesis]. The importance of these factors in determining plant geographical divergence has not been yet simultaneously evaluated. Senecio pterophorus (Asteraceae) is a perennial shrub native to eastern South Africa and a recent invader in western South Africa (since ˜100 years ago), Australia (>70–100 years) and Europe (>30 years). These areas differ in their summer drought stress [measured as the ratio of summer precipitation to potential evapotranspiration ( P /PET)] and their interactions with herbivores. We performed a common garden experiment with S. pterophorus sampled throughout its entire known distributional area to determine (i) whether native and non‐native populations diverge in their traits, as well as the plasticity of these traits in response to water availability and (ii) whether climate and herbivory play a role in the genetic differentiation across regions. Plants from the non‐native regions were smaller and had a lower reproductive output than plants from the indigenous area. No geographical differences in phenotypic plasticity were found in response to water availability. Herbivory was not related to the plant geographical divergence. In contrast, our results are consistent with the role of climate as a driver for postinvasive evolution, as suggested by adaptation of plants to a drought cline in the native range, the analogous change in plant traits in independently invaded regions and the convergence of vegetative traits between non‐native plants and native plants under similar drought conditions. Native and non‐native populations of S. pterophorus differed in plant traits, but not in trait plasticity, in response to their local climatic conditions. Our results are contrary to the role of herbivory as a selective factor after invasion and highlight the importance of climate driving rapid evolution of exotic plants. Abstract : Lay Summary